2006
DOI: 10.1126/science.1132661
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Prions in the Saliva and Blood of Deer with Chronic Wasting Disease

Abstract: A critical concern in the transmission of prion diseases, including chronic wasting disease (CWD) of cervids, is the potential presence of prions in body fluids. To address this issue directly, we exposed cohorts of CWD-naïve deer to saliva, blood, or urine and feces from CWD-positive deer. We found infectious prions capable of transmitting CWD in saliva (by the oral route) and in blood (by transfusion). The results help to explain the facile transmission of CWD among cervids and prompt caution concerning cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
435
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 456 publications
(465 citation statements)
references
References 24 publications
21
435
2
1
Order By: Relevance
“…A recent report showed that blood from CWD-infected deer contained infectivity and could transmit prion disease via a blood transfusion [50]. This finding recapitulates findings of blood infectivity transferred via transfusion from vCJD affected humans [61] and experimental from scrapie sick sheep [32], and indicates that prion transport throughout the body may include the blood as a potential vehicle.…”
Section: Cwd Prion Spread and Target Organssupporting
confidence: 77%
See 1 more Smart Citation
“…A recent report showed that blood from CWD-infected deer contained infectivity and could transmit prion disease via a blood transfusion [50]. This finding recapitulates findings of blood infectivity transferred via transfusion from vCJD affected humans [61] and experimental from scrapie sick sheep [32], and indicates that prion transport throughout the body may include the blood as a potential vehicle.…”
Section: Cwd Prion Spread and Target Organssupporting
confidence: 77%
“…Potential transmission mechanisms range from spread via direct contact among animals to environmental exposure through grazing in areas contaminated by prioninfected secretions, excretions (saliva, urine, feces), tissues (placenta), or decomposed carcasses. Recently, in a breakthrough finding, saliva from CWD-infected deer was shown to transmit prion disease [50]. An additional experiment by Miller et al showed that CWDinfected carcasses allowed to decay naturally in confined pastures can lead to CWD infections in captive deer, demonstrating the potential for environmental contamination to spread infection [55].…”
Section: Disease Control Challenges Posed By Cwdmentioning
confidence: 99%
“…Some endemic pockets have been notified. Body fluids are infectious and saliva is suspected to favor the horizontal, particularly efficient, dissemination of the disease [132]. At variance with scrapie, the placenta is poorly infectious, suggesting that transmission from mother-to-lamb might be rather low [135].…”
Section: Strain Diversity In Cwd?mentioning
confidence: 99%
“…Multiple studies showed that TSE infectivity is present in the blood of experimental rodents, sheep with natural and experimental scrapie and experimental BSE, and deer affected with chronic wasting disease (CWD) (15)(16)(17)(18)(19)(20). PrP TSE has been successfully detected in the following: in whole blood of experimentally infected mice and hamsters, in sheep with natural scrapie and experimental BSE, and in white-tailed deer afflicted with CWD (21)(22)(23); in buffy coats of hamsters and sheep experimentally infected with scrapie (24 -26), as well as in plasma of mice and hamsters with scrapie; and in sheep and white-tailed deer naturally and experimentally infected with scrapie and CWD, respectively (27)(28)(29)(30).…”
mentioning
confidence: 99%